Konsep Pengalaman Asali Paus Yohanes Paulus II dalam Konteks Kekerasan Seksual terhadap Perempuan di Indonesia - Emilianus Rango; Gabriel Putra Prima; Gregorius Bagung Santur; Iluminata Fatreimin Adur; Flavianus Joerdy Pati Klore (Jurnal Multidisiplin Indonesia, 2026)
This study seeks to analyze the concept of “original experience” proposed by Pope John Paul II and relate it to the phenomenon of sexual violence against women in Indonesia. The concept of “original experience” examines the unique dignity of human beings in the relationship between men and women. The main idea emphasized is that human beings are inherently equal in forming loving relationships without discrimination. However, social reality continues to show an increase in incidents of sexual violence against women. Through qualitative research methods using a literature review approach, this paper elaborates on the concept of original experience as an alternative perspective to address patriarchal culture, power imbalances, and weak legal protections that perpetuate sexual violence against women. This study also highlights that the misunderstanding of human dignity and equality in relationships often contributes to the persistence of violence against women in society. The findings indicate that a proper understanding of the concept of original experience can help reshape perspectives on women as individuals of dignity. Therefore, the implementation of this concept in social practice is crucial as an effort to prevent and address sexual violence against women.